Pengalihan Hak Atas Saham Perseoran Terbatas Melalui Hibah - I Wayan Suka Antara Yasa (Fakultas Hukum, Universitas Warmadewa, 2020)
This study aims to analyze how the procedure for transferring rights of shares to a limited company in its articles of association does not contain the provisions of Article 57 paragraph (1) of the Company Law and how the procedure for transferring rights of shares to a limited liability company is through a grant from parents to children. This research uses normative research with the statutory approach and conceptual approach. The data are collected by literature study and analyzed descriptively. The analysis shows that if the company's articles of association does not include the provisions of Article 57 paragraph (1) of the Company Law, the party that transfers the right is not obliged to: (a) offer beforehand to certain classification shareholders or other shareholders; (b) obtaining prior approval from the Company's Organs; and/or (c) obtain prior approval from the competent authority in accordance with statutory provisions; (2) Transfer of rights over shares through a grant from a parent to a child is not obliged to comply with the formulation of Article 57 paragraph (1) of the Company Law, especially regarding the approval of the company's organs, but in the case of changes in the structure of the company's management as a result of the transfer of rights over said shares, the party in the transfer of rights to shares must obtain approval at the General Meeting of Shareholders regarding the ability of the recipient of the transfer of rights to shares in carrying out their duties